(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate treatment response, survival outcomes, and safety of Atezolizumab plus Bevacizumab in patients with advanced hepatocellular carcinoma treated at Military Hospital 175. Subjects and methods: This retrospective case series with longitudinal follow-up included 20 patients with advanced hepatocellular carcinoma who received Atezolizumab plus Bevacizumab at Military Hospital 175 between March 2023 and August 2025. Treatment response was assessed according to RECIST version 1.1. Progression-free survival and overall survival were estimated using the Kaplan-Meier method. Results: The best overall response according to RECIST 1.1 consisted of 8 patients (40%) with partial response, 7 patients (35%) with stable disease, and 5 patients (25%) with progressive disease. The objective response rate was 40%, and the disease control rate was 75%. The median follow-up duration was 16.7 months (95% CI: 5.7-NR). Sixteen progression-free survival events (80%) and fourteen overall survival events (70%) were recorded. Median progression-free survival was 5.3 months (95% CI: 0.7-11.0), while median overall survival was 12.1 months (95% CI: 1.7-18.4). Grade 3-4 adverse events occurred in 10% of patients. The most common adverse events were fatigue (40%), hypertension (20%), elevated liver enzymes (15%), and bleeding (5%). Conclusion: Atezolizumab plus Bevacizumab demonstrated promising disease control in patients with advanced hepatocellular carcinoma, with an objective response rate of 40%, a disease control rate of 75%, a median progression-free survival of 5.3 months, and a median overall survival of 12.1 months. The safety profile was acceptable, with grade 3-4 adverse events observed in 10% of patients.